2023
DOI: 10.1080/09297049.2022.2162031
|View full text |Cite
|
Sign up to set email alerts
|

Do developmental dyslexia and congenital amusia share underlying impairments?

Abstract: Developmental dyslexia and congenital amusia have common characteristics. Yet, their possible association in some individuals has been addressed only scarcely. Recently, two converging studies reported a sizable comorbidity rate between these two neurodevelopmental disorders (Couvignou et al., Cognitive Neuropsychology 2019; Couvignou & Kolinsky, Neuropsychologia 2021). However, the reason for their association remains unclear. Here, we investigate the hypothesis of shared underlying impairments between dysle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 182 publications
0
4
0
Order By: Relevance
“…Overall, these previous studies and the current findings highlight the potential of fNIRS as a suitable neuroimaging technique to explore functional differences between children with DLD and TD children, and suggest that variations of cerebral activity in response to memory load manipulation could be an adequate neurophysiological marker. Future studies could investigate further the engagement of lateral frontal regions during auditory STM for musical and verbal material in children with DLD as deficits in STM for both materials have been observed (Couvignou et al, 2023; Couvignou & Kolinsky, 2021; Forgeard et al, 2008; Ziegler et al, 2012). In the long term, a better understanding of the neural mechanisms underlying auditory STM in DLD and their link to the processes reported to be impaired in this population (e.g., syntax processing, phoneme discrimination, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, these previous studies and the current findings highlight the potential of fNIRS as a suitable neuroimaging technique to explore functional differences between children with DLD and TD children, and suggest that variations of cerebral activity in response to memory load manipulation could be an adequate neurophysiological marker. Future studies could investigate further the engagement of lateral frontal regions during auditory STM for musical and verbal material in children with DLD as deficits in STM for both materials have been observed (Couvignou et al, 2023; Couvignou & Kolinsky, 2021; Forgeard et al, 2008; Ziegler et al, 2012). In the long term, a better understanding of the neural mechanisms underlying auditory STM in DLD and their link to the processes reported to be impaired in this population (e.g., syntax processing, phoneme discrimination, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of verbal STM has been shown to be a hallmark of language-related learning disorders, such as dyslexia (Majerus & Cowan, 2016;Roodenrys & Stokes, 2001;Ziegler et al, 2009Ziegler et al, , 2011 and Developmental Language Disorder (DLD, Archibald & Gathercole, 2006;Nickisch & Von Kries, 2009;Nithart et al, 2009). A few studies have also observed impairment for musical STM in dyslexic children (Couvignou et al, 2023;Forgeard et al, 2008;Ziegler et al, 2012). Moreover, recent studies have shown a sizeable comorbidity (~30%) between dyslexia and congenital amusia (in both adults: Couvignou et al, 2019, andchildren: Couvignou &Kolinsky, 2021;Couvignou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the redescription-associate learning paradigm focused on the dissociation between implicit and explicit processes, it may have clinical implications beyond amusia. As a neurodevelopmental disorder, amusia is akin to other neurodevelopmental disorders such as developmental dyslexia with impairment in reading and congenital prosopagnosia with impairment in face recognition (Couvignou & Kolinsky, 2021;Couvignou et al, 2019Couvignou et al, , 2023Mignault Goulet et al, 2012;Peretz, 2016). Specifically, dyslexics or prosopagnosics exhibit intact implicit but impaired explicit processing of phonemes (Bonte & Blomert, 2004;McPherson et al, 1998;Mundy & Carroll, 2012) or faces (Eimer et al, 2012;Rivolta et al, 2012;Stumps et al, 2020) respectively.…”
Section: Discussionmentioning
confidence: 99%